Information needs, expectations, and treatment preference of patients considering spinal surgery: A case-control survey. (November 2022) - Lam, William Wing-Kuen; Yuen Loke, Alice; Wong, Chun-Kwan; Luk, Bronya Hi-Kwan
Abstract: Study design: Case-control survey. Objectives: To explore intrapersonal factors associated with decision of patients with degenerative back pain for surgery. Methods: From September 2018 to May 2019 patients were invited to complete a questionnaire. Patients who decided on (case) and declined surgery (control) were later confirmed from medical records. Results: Seventy-five patients were recruited. Male patients (75.0%, p  = 0.019), those who were married (78.7%, p  = 0.0045), and had spousal care-givers (89.2%, p  < 0.0001) were more likely to decide for surgery. All patients who decided on surgery expressed need for information on "the severity of their spine conditions" ( p  = 0.039). Those who decided on surgery did not have as the high expectation on "to sleep more comfortably" as those who declined (4.71 vs. 4.91, p  = 0.022). The predictive factors for surgery decision by logistic regression analysis were: male gender (OR = 3.23, 95% CI: 1.19–8.77, p  = 0.021); married (OR = 5.231, 95% CI: 1.87–14.61, p  = 0.002); with available spousal care-giver (OR = 1.85, 95% CI: 0.198–3.89, p  = 0.031); and those who preferred to treat/cure the spine disorder by pharmacological treatment (OR = 2.77, 95% CI: 1.02–7.50, p  = 0.045). Conclusion: Patients who decided on surgery were likely to indicate need of medical information related to their condition. Patients were in hope of better relief of physical symptoms, especially related to sleep comfort. Patients would escalate their treatment from conservative to surgery when conservative treatments were no longer effective.